Methods for Selection of Prioritized Elements in Quality Management of Health Services - Budi Susatia; Heru Santoso Wahito NUGROHO (Health Notions, 2020)
Methods for Selection of Prioritized Elements in Quality Management of Health Services -------- -------- (invited by editor)